2014
DOI: 10.5505/abantmedj.2014.25338
|View full text |Cite
|
Sign up to set email alerts
|

Aeroalergen distribution in skin prick test in children who were diagnosed with asthma and allergic rhinitis in Malatya region.

Abstract: Amaç: Astım ve alerjik rinit tanısı konulmuş çocukların aeroalerjenlere karşı duyarlılıkların dağılımını belirlemektir. Yöntem: İnönü Üniversitesi Pediatrik Alerji ve Astım polikliniğinde Haziran 2012 ile Mayıs 2013 tarihleri arasında astım ve alerjik rinit tanısı konulan çocukların dosyaların-dan deri prik test sonuçları geriye dönük olarak incelendi. Bulgular: Deri prik testi yapılan 358 hastanın 229 (%64) u en az bir aeroalerjene karşı duyarlı idi. Deri testinde pozitiflik tespit edilen hastaların ortanca y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…As has been reported in previous studies, the awareness and knowledge level of EAIs was inadequate among participants in this study (Prince et al, 2018;Topal et al, 2014;González-Díaz, et al, 2021;Yildiz et al, 2022). We analyzed and compared the percentages of FPs with adequate knowledge regarding diagnosis, acute treatment, and EAIs, our results indicate that older age and longer duration of work experience did not significantly influence knowledge of anaphylaxis, similar to the results of a previous study in Turkey (Topal et al, 2014;Yildiz et al, 2022). In contrast to recent study by Arga et al (2021), having clinical experience with or without epinephrine treatment had no statistically significant impact on the rates of adequate knowledge among participants in our study.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…As has been reported in previous studies, the awareness and knowledge level of EAIs was inadequate among participants in this study (Prince et al, 2018;Topal et al, 2014;González-Díaz, et al, 2021;Yildiz et al, 2022). We analyzed and compared the percentages of FPs with adequate knowledge regarding diagnosis, acute treatment, and EAIs, our results indicate that older age and longer duration of work experience did not significantly influence knowledge of anaphylaxis, similar to the results of a previous study in Turkey (Topal et al, 2014;Yildiz et al, 2022). In contrast to recent study by Arga et al (2021), having clinical experience with or without epinephrine treatment had no statistically significant impact on the rates of adequate knowledge among participants in our study.…”
Section: Discussionmentioning
confidence: 47%
“…Current guidelines recommend that individuals who have experienced anaphylaxis and those at risk of anaphylaxis should be prescribed and carry an EAI at all times for emergency use (Cardona et al, 2020;Muraro et al, 2022). As has been reported in previous studies, the awareness and knowledge level of EAIs was inadequate among participants in this study (Prince et al, 2018;Topal et al, 2014;González-Díaz, et al, 2021;Yildiz et al, 2022). We analyzed and compared the percentages of FPs with adequate knowledge regarding diagnosis, acute treatment, and EAIs, our results indicate that older age and longer duration of work experience did not significantly influence knowledge of anaphylaxis, similar to the results of a previous study in Turkey (Topal et al, 2014;Yildiz et al, 2022).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The hot and dry climate of the Şanlıurfa region, which is predominantly agricultural, explains the high frequency of detection of sensitization to grass pollens on skin tests in our study. In previous studies in the regions of Malatya (48.9%), Adıyaman (77.5%), and Diyarbakır (70.4%), which have a similarly hot and dry climate, sensitivity to pollen (grass and cereal mixtures) has been most frequently reported ( 4 , 18 , 19 ). In another study in Şanlıurfa (n= 38), the most common allergen sensitivities have been found as grass (39.5%) and cereal mixtures (34.2%) ( 20 ).…”
Section: Discussionmentioning
confidence: 95%